Działalność Studenckiego Koła Naukowego „Żuraw” w roku akademickim 2018/2019 - Kwiatkowski, Czesław; Galiński, Przemysław; Kuźma, Martyna (Lodz University of Technology. Faculty of Civil Engineering, Architecture and Environmental Engineering, 2019)
Artykuł zawiera informacje dotyczące działalności i charakterystyki Studenckiego Koła Naukowego „Żuraw”. Przedstawiono najważniejsze wydarzenia, jakie miały miejsce w roku akademickim 2018/2019. W artykule zawarto relacje z odbytych wycieczek na budowy, konkursów, w których uczestniczyli członkowie koła, działalności realizowanej we współpracy z innymi organizacjami, instytucjami i firmami. Poruszono także kwestie wydarzeń okolicznościowych i marketingu.

The article discusses the activity and characteristics of Students’ Research Group „Crane” („Żuraw”). It presents the most important events that were held in the academic year 2018/2019. The article reports on the visits to the construction sites, competitions in which the members of SKN Żuraw participated, the activities in collaboration with other organizations, institutions and companies, occasional events and marketing.